WRITING IS ONE OF ESSENTIAL PART IN TEACHING FOREIGN LANGUAGES - Xodjayorova Sayora Abdullaevna; Bekkulova Hojar Zayniddinova (International Journal of Innovations in Engineering Research and Technology, 2021)
Thearticle under discussion depicts methods of teaching writing in teaching foreign languages. The author of the article suggests several interesting activities which facilitate and motivate learning of foreign languages.